(untitled) (Global Journal of Human-Social Science, 2020)
This paper analyses the governance structures of the international financial system, focusing on the International Monetary Fund and the World Bank. Therefore, this study elucidates the functioning of these institutions through an analysis of its power structures. First, we examine the origins, evolution, and the institutional structure of these organizations. Second, we perform a literature review on the governance of international institutions to highlight the most appropriate theories to analyze the object in question. Then, we examine the cases in question through the Principal-Agent theory.